CAREGIVERS’ NEEDS IN CARING FOR RELATIVES WITH SCHIZOPHRENIA IN MEDAN INDONESIA: A PHENOMENOLOGICAL STUDY - Jenny Marlindawani Purba (Belitung Nursing Journal, 2017)
Background: A caregiver is a primary nurse and has a major role in providing care for people with schizophrenia. Caring for those with schizophrenia for a long period of time is challenging for families, especially for caregivers. Various needs ought to be studied by nurses to assist caregivers in providing optimal care for family members who experience schizophrenia. Objective: This qualitative study aims to explore the needs of caregivers in treating schizophrenia at home. Methods: This study employed a phenomenological study design. A total of 10 respondents were selected using a purposive sampling with criteria: 1) having family members diagnosed with schizophrenia, 2) directly involved in taking care of patients at home, 3) caring for patients with schizophrenia for more than one year, 4) willing to be a participant by signing an informed consent, and 4) being able to identify what is needed in treating schizophrenia. Colaizzi’s method was used to analyze the data. Results: There were four themes of the caregivers need in caring for schizophrenia patients at home, including 1) seeking information about schizophrenia, 2) sought healing through regular treatment, 3) looking for appropriate rehabilitation for relatives with schizophrenias, and 4) utilizing mental health facilities. Conclusions: It is expected that nurses have the knowledge and skills in identifying and helping the families, especially the caregivers, to meet unmet needs so they can optimize home care.